2023
DOI: 10.3390/plants12040782
|View full text |Cite
|
Sign up to set email alerts
|

Protein Mass Fingerprinting and Antioxidant Power of Hemp Seeds in Relation to Plant Cultivar and Environment

Abstract: Cannabis sativa (hemp) seeds are considered a functional food for their favorable contents of essential fatty acids, proteins and antioxidants. Beyond phenolics and carotenoids, the bioactivity of proteins has recently been investigated. However, plant genotype and environmental conditions can affect quantity and quality of macronutrients and phytochemicals in seeds, influencing their nutraceutical properties. In this study, the effects of plant variety and seed origin on the protein profile and antioxidant ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Hemp seeds also exhibit antioxidant properties. Cattaneo et al reported that minerals, such as potassium, magnesium, and calcium are found in hemp seeds, alongside phytochemicals with antioxidant activity, such as tocopherols and lignan derivatives [11] Additionally, Giacomo et al reported the antioxidant and anti-inflammatory effects of hemp water extract on mouse fibroblasts and keratinocytes via metabolomic profiling [12]. Similarly, there are numerous reports on the antioxidant or other beneficial effects of hemp derivatives, such as extracts and oil, especially on the skin, and for cosmetic applications [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Hemp seeds also exhibit antioxidant properties. Cattaneo et al reported that minerals, such as potassium, magnesium, and calcium are found in hemp seeds, alongside phytochemicals with antioxidant activity, such as tocopherols and lignan derivatives [11] Additionally, Giacomo et al reported the antioxidant and anti-inflammatory effects of hemp water extract on mouse fibroblasts and keratinocytes via metabolomic profiling [12]. Similarly, there are numerous reports on the antioxidant or other beneficial effects of hemp derivatives, such as extracts and oil, especially on the skin, and for cosmetic applications [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Hemp seeds also exhibit antioxidant properties. Cattaneo et al reported that minerals, such as potassium, magnesium, and calcium are found in hemp seeds, alongside phytochemicals with antioxidant activity, such as tocopherols and lignan derivatives [ 11 ] Additionally, Giacomo et al reported the antioxidant and anti-inflammatory effects of hemp water extract on mouse fibroblasts and keratinocytes via metabolomic profiling [ 12 ]. Similarly, there are numerous reports on the antioxidant or other beneficial effects of hemp derivatives, such as extracts and oil, especially on the skin, and for cosmetic applications [ 13 – 16 ].…”
Section: Introductionmentioning
confidence: 99%